Margin ACcentuation for resectable Pancreatic cancer using Irreversible Electroporation – Results from the MACPIE-I study. Issue 10 (October 2021) - Kundalia, Kaushal; Hakeem, Abdul; Papoulas, Michail; Mcphail, Mark; Reddy, Shruthi; Peddu, Praveen; Kibriya, Nabil; Atkinson, Simon; Prachalias, Andreas; Srinivasan, Parthi; Heaton, Nigel; Sarker, Debashis; et al.
Abstract: Introduction: Margin accentuation (MA) using Irreversible electroporation (IRE) offers an unique opportunity to reduce the R1 resections in resectable pancreatic cancer (RPC). This study aims to assess the rate of margin positivity using IRE for MA during pancreaticoduodenectomy (PD) for resectable pancreatic head tumours. Materials and methods: Following ethical approval, MA using IRE was carried out in 20 consecutive patients to posterior and superior mesenteric vein (SMV) margin, and the pancreatic neck, prior to the PD resection. The control group (non-IRE; n = 91) underwent PD without MA over the study period, March 2018 to March 2020. Results: There was no difference between the two groups in terms of patients' age, gender, pre-op biliary drainage, site of malignancy or pre-operative TNM stage. The overall margin positive rate for IRE group was lesser (35.0%) when compared to non-IRE group (51.6%; p = 0.177), with significantly less posterior pancreatic margin positivity (5.0% vs. 25.3%; p = 0.046). When only treated margins (SMA margin excluded) were compared, the IRE group had significantly lower margin positive rates (20.0% vs. 51.6%; p = 0.013). There was no difference between the two groups in terms of intra- or post-operative complications. With a median follow-up of 15.6 months, the median DFS and OS for IRE and non-IRE groups were 17 and 18 months (p = 0.306) and 19 and 22 months (p = 0.227) respectively. Conclusion: Our pilot study confirms the safety of MA using IRE for RPC, with reduction in margin positivity. These results as a proof of concept are promising and need further validation with a randomised controlled trial.